Pengaruh Penerapan E-Filing, Pengetahuan Perpajakan Dan Pelayanan Fiskus Dalam Penyampaian Spt Tahuanan Ditengah Pandemi Covid-19 Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kpp Pratama Pare - Nofa Melinda Indrianto; Indrian Supheni; Moh Ali Lutfi; Wiwin (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to determine the effect of implementing e-filing and tax knowledge in the submission of annual tax returns in the midst of the covid-19 pandemic on individual taxpayer compliance at KPP Pratama Pare. The population in this study are individual taxpayers in the Nganjuk Regency area. Data was collected primarily by distributing questionnaires, the number of samples taken was 100 respondents using the simple random sampling method (simple random sampling). The technique used in this study is linear regression analysis where data processing uses SPSS version 25. The results of this study indicate that e-filling and tax service services have a significant effect on individual taxpayer compliance. Meanwhile, tax knowledge has no significant effect on individual taxpayer compliance